2022
DOI: 10.12944/cwe.17.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Fruit Crops- A Review

Abstract: Climate change is becoming an observed reality. Several researchers around the world have been working for decades to model predicted climatic changes that will occur in the 21st century and forecast the potential impact on the global eco-system. Climate plays a major role in deciding perennial fruit crop’s distribution, phenology, fruit quality, and disease and pest incidents. Physiological and yield attributes of fruits are sensitive to changing global climate as the climatic factors such as temperature rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It has been reported that fruit crops are particularly vulnerable to climate change as compared to field crops due to their extended flowering period. Alterations in climatic parameters have had a significant influence on the growth and development of fruit crops, resulting in changes in flowering patterns, modifications in fruit quality, and shifts in disease incidence [ 130 ].…”
Section: Impact Of Climate Change On Mycotoxin Contaminationmentioning
confidence: 99%
“…It has been reported that fruit crops are particularly vulnerable to climate change as compared to field crops due to their extended flowering period. Alterations in climatic parameters have had a significant influence on the growth and development of fruit crops, resulting in changes in flowering patterns, modifications in fruit quality, and shifts in disease incidence [ 130 ].…”
Section: Impact Of Climate Change On Mycotoxin Contaminationmentioning
confidence: 99%